(untitled) (e-Journal of Linguistics, 2020)
Speakers will usually choose the appropriate code (certain languages, dialects, or variations of the same language) when communicating. The use of code switching by inserting English words, phrases, sentences, or clauses into Indonesian utterances is the implication of a bilingual speaker. This paper aims at analyzing the types and factors of using code switching by male participants and female participants in Indonesian TV talk shows. Data in this study is taken from a corpus of transcribed spoken text (82.270 words in total) from total 17 episodes from two talk shows aired on two different television programs. The results show that female and male participants in their roles as hosts, guests, and co-host switch codes in their speech. They can be said to be creative and innovative speakers